"Their wounds are our wounds": a case for affective solidarity between Palestine and Kashmir. Issue 3 (3rd May 2020) - Zia, Ather
ABSTRACT: Both Palestine and the Indian held Kashmir have become hallmarks of a postcolonial siege manifest in heavy militarisation, illegal occupation, human rights violations, and an excruciating love born from and for people's resistance and solidarity. While different, strong overlaps exist between the two conflicts in having been midwifed by the waning British Empire in 1947; subsequent internationalisation and fighting against a type of contemporary international politics that subsumes them under so-called 'Islamic terrorism.' Also noticeable is the motif of 'suffering' that makes the tragedy of Kashmir resonate with the pathos of Palestine. This paper focuses on the vantage from Kashmir, where people herald the Palestinian struggle as pioneering and a beacon of just struggle. I illustrate how Kashmiris, have come to harbour for the Palestinians an 'affective solidarity' which is evident in their modes of resistance to lend support for the liberation of Palestine and credibility to the Kashmir's own resistance movement.